Comparative Study Of Effect Of Various Parameters Affecting Growth And Physiology Of Normal Flora Of Human & Animal Git With Commercial Probiotics - ARCHANA RANA; NEEPA PANDHI; MRUGESH KHUNT (International Journal of Pharma and Bio Sciences, 2012)
Probiotics are the normal gut flora of human which may get affected by several growth conditions. These characteristics include the demonstration of bile tolerance, acid resistance and antibiotic resistance. The primary objective of this work is to compare commercially available products of probiotics with normal flora of human and animal origin as well as microbes in milk and milk products. Further study involves the study of colony and morphological characteristics of the selected organisms and study of their salt, pH and Bile tolerance. Effect of presence and absence of probiotics on the growth pattern of the organism is significant. All these characters were comparatively analysed to establish potent organism as a probiotics in GIT. 21 natural samples comprised of stool samples, vaginal swabs, cow dung and milk & milk products were the natural samples selected which were compared with 7 commercially available probiotics. Natural samples were having bacilli, cocci and yeast while commercial samples were having bacilli and cocci. The isolates from natural samples proved to be having higher growth and survival as compared to commercially available probiotics with the effect of salt, bile salt and pH. The uses of prebiotics enhanced the growth of both natural as well as commercial isolates.